The Use of Intraosseous Screw for Upper Molar Distalization: A Case Report - Polat-Özsoy, Ömür (European Journal of Dentistry, 2008)
The use of implants has made a major change in orthodontic treatment mechanics. They have replaced conventional unaesthetic and compliance dependent extraoral appliances with well accepted intraoral mechanics. Implants can be used in molar and canine distalization, intrusion and in extraoral force applications. In the present case report, treatment of a case using an intermaxillary fixation screw (IMF) will be presented. The treatment results will be evaluated using pretreatment, post distalization and post treatment cephalometric radiographs and dental casts. (Eur J Dent 2008;2:115-121)
Keywords: Dental erosion; Citric acid; Non-carious cervical lesion